Australian Carabid Beetles XII. More Tachys - P. J. Darlington (Psyche: A Journal of Entomology)
This is, in effect, a continuation of Part X1 (Darlington 1962) of my series of short papers on Australian Carabidae. The present part deals with some additional groups of Tarhys.